Finding Magnetopause Standoff Distance Using a Soft X‐Ray Imager: 1. Magnetospheric Masking. Issue 12 (23rd December 2022) - Samsonov, Andrey; Carter, Jennifer Alyson; Read, Andrew; Sembay, Steven; Branduardi‐Raymont, Graziella; Sibeck, David; Escoubet, Philippe
Abstract: The magnetopause standoff distance characterizes global magnetospheric compression and deformation in response to changes in the solar wind dynamic pressure and interplanetary magnetic field orientation. We cannot derive this parameter from in situ spacecraft measurements. However, time series of the magnetopause standoff distance can be obtained in the near future using observations by soft X‐ray imagers. In two companion papers, we describe methods of finding the standoff distance from X‐ray images. In Part 1, we present the results of MHD simulations which we use for the calculation of the X‐ray emissivity in the magnetosheath and cusps. Some MHD models predict relatively high density in the magnetosphere, larger than observed in the data. Correcting this, we develop magnetospheric masking methods to separate the magnetosphere from the magnetosheath and cusps. We simulate the X‐ray emissivity in the magnetosheath for different solar wind conditions and dipole tilts. Plain Language Summary: The highly dynamic solar wind continuously bombards the Earth's magnetosphere, which changes shape in response. The magnetopause is the outer boundary of the magnetosphere, which is known to move. We are limited in our knowledge of the overall shape of the magnetopause, as current in situ measurements can only tell us about any change in the magnetopause at one specific location. Spacecraft carrying soft X‐ray imagers, however, will soon revolutionize our understanding by monitoring large areas of the magnetopause as the solar wind varies. In this first of a series of two papers, we simulate X‐ray emissions in the vicinity of the Earth using two magnetohydrodynamic models, and for two case studies with vastly different incoming solar wind conditions. In a subsequent paper, we examine methods how to extract the magnetopause shape from the simulated X‐ray images. Key Points: The SMILE mission will carry soft X‐ray imager onboard Magnetospheric masking methods separate the magnetosphere from the magnetosheath and cusps We make magnetospheric masks using threshold conditions and flowlines